Steering of sub-GeV positrons by ultrathin bent silicon crystal for ultraslow extraction applications - M. Garattini; D. Annucci; P. Gianotti; A. Liedl; E. Long; M. Mancini; T. Napolitano; M. Raggi; P. Valente (Physical Review Accelerators and Beams)
For the first time at the Beam Test Facility (BTF) of the DAΦNE accelerator complex at the Laboratori Nazionali di Frascati of INFN, 450 MeV positrons have been deflected with high efficiency, using the planar channeling process in a bent silicon crystal. The deflection angle obtained is beyond 1 mrad. This interesting result finds several applications for manipulation of this kind of beams, in particular for ultraslow extraction from lepton circular accelerators like DAΦNE. In this work, the experimental apparatus, the measurement procedure, and the experimental results are reported.